ANALISIS HUBUNGAN ASET PAJAK TANGGUHAN TERHADAP INDIKATOR KEUANGAN DAN EKONOMI PERUSAHAAN AGRIKULTUR DI INDONESIA (Studi Empiris Perusahaan Agrikultur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2018-2022) - Fadillah, Aulya Zahra; Kiswara, Endang (Diponegoro Journal of Accounting, 2024)
This study aims to find empirical evidence whether the relationship between the Analysis of the Relationship between Deferred Tax Assets on Economic and Financial Indicators of Agricultural Companies Listed on the Indonesia Stock Exchange in 2018-2022.The independent variables used in this study include current liquidity ratio, general liquidity ratio, Return on equity (ROE), and Debt to Equity Ratio (DER). While the dependent variable used in this study is deferred tax assets. This study has a population consisting of all agricultural companies in Indonesia listed on the Indonesia Stock Exchange for the period 2018 to 2022. Sampling is based on the use of simple random sampling method so that the number of research samples used is 50 samples of companies. This study uses multiple regression analysis methods in hypothesis testing.The results of this study indicate that there is no significant relationship between deferred tax assets and current liquidity, general liquidity ratio, Return On Equity (ROE). While there is a significant relationship between deferred tax assets and debt to equity ratio (DER).